Exitomania, the propaganda machine that can destroy the European Union - Tasente, Tanase; Rus, Mihaela (Technium Social Sciences Journal, 2019)
Euroscepticism has worsened among the member countries, and an opinion poll conducted by the Pew Research Center, on a sample of 10,491 respondents from 10 EU countries and published shows that in 2 member countries - France and Greece - 61% and 71% of the citizens regard the European Union in a negative sense. This unfavorable perception regarding the future of the European Union has spread and was immediately exploited by political parties from different countries that have been voted in the European Parliament. Thus, we can see that the Euro-Parliamentary groups with Eurosceptic ideologies started to grow fast and according to the configuration of the 2019 European Parliament, we can see that the eurosceptics gain more strength. Through this research, we set out to analyze the degree of online interest regarding keywords related to EU leaving, in 8 countries of the European Union: The Netherlands (Nexit), United Kingdom (Brexit), France (Frexit), Greece (Grexit), Ireland (Irexit), Spain (Spexit), Italy (Italexit) and Sweden (Swexit). In order to reach the research objectives, we collected the data on the online interest from the Google Trends website (the evolution over time regarding Euroscepticism in the European Union, the maps regarding the regions of the 8 countries monitored with the highest degree of online interest for "EU leaving", and the most searched keywords in each country regarding leaving the European Union). The monitoring period is January 2004 – July 2019.